Peran Pertumbuhan Pasar Modal Syariah Dalam Peningkatan Perekonomian Indonesia - Ahmad Kharisul Muslih; M. Ahsan Taufiki; Agus Eko Sujianto (Universitas Maritim AMNI Semarang, 2023)
Sharia financial instruments continue to increase every year, including the Islamic capital market which has also experienced a significant increase. The Islamic capital market has one of the most important instruments, namely Islamic stocks. The capital market has been viewed by the world and has been used as an important instrument that every country must develop, it can be remembered for its important role in helping the economy. In writing this article using the library research method. By using the documentation data collection method, namely by quoting or recording directly from the website of the Financial Services Authority www.ojk.go.id and the Central Bureau of Statistics www.bps.go.id. The results of this study show that the strong and increasing role of the Islamic capital market in shaping the capitalization of the Indonesian capital market indicates that the Islamic capital market plays an important and significant role in driving the rate of economic growth in Indonesia.